Fundamentals of quality control and improvement - Mitra, Amitava (John Wiley & Sons, Inc., 2021)
"The nation is revolutionizing quality in all sectors and phases. Quality is one of the key elements in surviving the tough competition faced in domestic and international markets. Consequently, this has created the need for producing technically competent people who are well-versed in statistical quality control and improvement. This need is more critical now than it has ever been. It has an impact on college and university curricula in disciplines such as business, management, technology, and engineering. This book integrates service sector examples throughout. This book integrates statistical concepts to decision making in the realm of quality assurance. With the growing importance of the field of health care, concepts, tools, techniques, and issues in the domain of health care quality are addressed in several chapters. Display and analysis of customer satisfaction data, through surveys, is included. Strategic implications on decision making, based on the degree of satisfaction and the degree of importance of survey items are presented. Risk-adjusted variable control charts, such as the risk-adjusted cumulative sum chart, risk-adjusted sequential probability ratio test, risk-adjusted exponentially weighted moving average chart, and the variable life-adjusted display chart are presented. Risk-adjusted attribute control charts, unique to this book, among others, are discussed. This includes, for example, risk-adjusted p-chart and risk-adjusted u-charts. Monitoring of low occurrence nonconformities through a g-chart is included. The only book at this level that incorporates concepts of survival analysis, which is quite relevant to health care"--